A constituição da cenografia e do ethos discursivo como dispositivos argumentativos em sinopses literárias - Iumatti, Jacqueline de Paula Sbeghen (2024)
This Dissertation is inserted in the theoretical-methodological postulates of French Discourse Analysis (AD), in the approaches of Maingueneau (2020; 2018; 2013; 2011; 2010; 2008), to deal with the genre of discourse and its enunciator under the categories of enunciative scene and discursive ethos. The objective of the study is to examine how the construction of the scenography and the constitution of the discursive ethos function as argumentative devices in the literary synopsis genre published in the flap of a collection of texts by Clarice Lispector, released in 2020. The theme is relevant because, through the enunciative-discursive perspective, we observe how the enunciator can imprint different scenography in his speech and construct different discursive ethos, to create effects of meaning that validate the 2020 edition and relegitimize the reading of a 20th century author for the public of current co-speakers. The proposed analysis is based on a theoretical-methodological procedure in which, based on selected excerpts, different scenography and discursive ethos can be inferred in which cultural discourse and academic discourse hide the dissemination discourse, typical of the editorial market that seeks to promote , with a greater or lesser degree of empathetic relationship with the cospeaker, the sale of the book product